2015
DOI: 10.1111/ijfs.12937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cofermentation and sequential inoculation of Saccharomyces bayanus and Torulaspora delbruckii on durian wine composition

Abstract: Summary This work investigated the effects of cofermentation and sequential inoculation of Torulaspora delbrueckiiBiodiva and Saccharomyces bayanusEC‐1118 on chemical and volatile components of durian wines. Cofermentation and sequential inoculation resulted in higher production of ethanol (6.2% and 7.7% v/v, respectively) relative to the control (5.3% for S. bayanus and 5.8% for T. delbrueckii). Further, cofermentation and sequential inoculation produced higher amounts of acetyl esters and higher alcohols esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
4
11
0
Order By: Relevance
“…The early degradation in AF only (day 2 to day 7) could be caused by the biochemical metabolism related to the production of ATP and the regeneration of NAD(P) + in energy conservation (Jackowetz & Mira de Orduña, 2012). A relatively lower level of pyruvic acid (0.12 g/L) was accumulated in the S. cerevisiae EC-1118 control than in the T. delbrueckii Biodiva control (0.25 g/L), which agrees with our previous results (Lu et al, 2015). In addition, pyruvic acid could be metabolised by S. cerevisiae into acetaldehyde and further to ethanol (Wang et al, 2015 Fig.…”
Section: Changes In Organic Acidssupporting
confidence: 91%
See 1 more Smart Citation
“…The early degradation in AF only (day 2 to day 7) could be caused by the biochemical metabolism related to the production of ATP and the regeneration of NAD(P) + in energy conservation (Jackowetz & Mira de Orduña, 2012). A relatively lower level of pyruvic acid (0.12 g/L) was accumulated in the S. cerevisiae EC-1118 control than in the T. delbrueckii Biodiva control (0.25 g/L), which agrees with our previous results (Lu et al, 2015). In addition, pyruvic acid could be metabolised by S. cerevisiae into acetaldehyde and further to ethanol (Wang et al, 2015 Fig.…”
Section: Changes In Organic Acidssupporting
confidence: 91%
“…Previous studies have reported that T. delbrueckii possessed good fermentation efficiencies with residual sugar levels of less than 2 g/L and produced comparable levels of ethanol to S. cerevisiae when fermented at 20°C (Lu et al, 2015(Lu et al, , 2016a. Further, T. delbrueckii showed a better capacity for producing higher alcohols and ethyl esters, which could contribute to the fruity notes and aroma complexity of the wines (Lu et al, 2016a).…”
Section: Introductionmentioning
confidence: 95%
“…The analysis of aromatic compounds showed that independent of yeast strain, the total concentration of higher alcohols was below the 300 g/L reported by several authors as a limit below which higher alcohols contribute positively to wine aromatic complexity (Guth and Sies ). Despite it, wines prepared from T. delbrueckii and mixed cultures showed a lower overall higher alcohol concentration corroborating the results reported by Rojas et al (), Azzolini et al () and Lu et al (). As previously reported by Azzolini et al () and Lu et al () using other strains of T. delbrueckii, wines fermented with TPI‐4 exhibited the highest concentration of 2‐phenylethanol, the only higher alcohol considered to be aromatically positive.…”
Section: Discussionsupporting
confidence: 90%
“…Volatile compounds were analysed using a headspace solid-phase microextraction (SPME) method coupled with gas chromatography-mass spectrometer and flame ionization detector (GC-MS/FID), as reported by Lu et al [12]. Liquid juice or wine samples were centrifuged, and the pH was adjusted to 2.5 by 1 M HCl, and a 5 mL sample was sealed in a 20-mL vial with a septum lined with polytetrafluoroethylene (PTFE).…”
Section: Analysis Of Volatile Compounds With Gc-ms/fidmentioning
confidence: 99%